1989
DOI: 10.1016/0014-5793(89)80114-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the SmB′ splicing protein in rodent cells capable of following an alternative RNA splicing pathway

Abstract: The expression of the SmB and SmB' spliceosome proteins in a variety of cell types and tissues has been investigated. Although SmB is found in all cells studied, the StuB' protein is found only in a small number of rodent cell types. The presence of this protein is correlated with the ability to utilize an alternative pathway of RNA splicing which is not available in most cell types. This is the first demonsIration of tissue specific expression of a protein component of the spliceosome and suggests a role for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Since we have previously shown that this tissue expresses StuB but not SmB' [9], this RNA is likely to encode the SmB protein.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Since we have previously shown that this tissue expresses StuB but not SmB' [9], this RNA is likely to encode the SmB protein.…”
Section: Resultsmentioning
confidence: 91%
“…1.6 kb and 1.4 kb were detected the larger of which was present at considerably greater abundance. Since PCC3 cells in common with other EC cells express both the tissue specific StuB' protein and the constitutively synthesized SmB protein [9,10], it is likely that the larger transcript encodes the tissue specific B' protein. The RNA samples gave identical single bands when hybridized with probes specific for other RNA species such as that encoding cytochrome oxidase indicating that the difference in the pattern obtained with the K5-1 probe was not due to RNA degradation (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations